Računalniško preverjanje ustreznosti zaščitne naprave pred podletom motornih tovornih vozil - Ren, Zoran (Strojniški vestnik, 1999)
This paper describes the fundamentals of the present situation and explores the possibilities of new computational safety inspection procedures for rear underrun protection devices (RUPDs), which are essential for the approval o loadcarrying vehicles. A RUPD is required to comply with the ECE R 58 regulation, which provides strict requirements in terms of device design and its behaviour under loading. The regulation allows for computational safety inspection of the protection device, which has prompted research into exporing the possibilities for computational simulation of RUPD behaviour under loading. This paper describes the conditions and procedures for proper computational simulations, which are based on the FEM. At this early stage of research only the elastic response of the studied RUPD is considered in the computational analyses. The studied safety device has also been experomentally tested. Reasonably good agreement of computational and experimental results leads to the conclusion that computational analyses can be used for inspection of a RUPD.
Keywords: motorna vozila; numerične metode; zaščita; preizkušanje; računalniška simulacija